MAKNA PROPERTI TARI JEPIN TALI BINTANG DI DESA KALIMAS KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA - Silvananda Dwi Varadibtya; Ismunandar Ismunandar; Winda Istiandini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This research was conducted because of researchers' concerns about the authenticity of Jepin Tali Bintang Dance property in Kalimas Village, which in the future does not rule out change. Therefore, this study aims to determine the shape and meaning that needs to be revealed in terms of the unique in Jepin Tali Bintang dance property. The method that is utilized is descriptive method with qualitative research and also semiotic approach. The collection technique in the form of observation, interview, and documentary study. Data validation technique that is used by conducting the extended observation and triangulation source. Based on the data analysis can be concluded that the meaning of Jepin Tali Bintang Dance property has a message that wanted to be delivered to the society in Kalimas Village especially to the muslims. Jepin Tali Bintang Dance property with pentagon shape where has which is means the five Pillars of Islam. The yellow painting property symbolize Pontianak Kadariah Palace. The property hanging above the dancer depicts the stars in the sky, the 8 of ropes that is used mean sense of kinship that connecting to each other. The various colors on the rope consists of 4 colors, namely white, red, yellow and green, each color has a different meaning. The meaning of all Jepin Tali Bintang properties are interconnected with each other and has related with the daily life of the people in Kalimas Village, especially for Muslims.